Perencanaan Karir Mahasiswa Semester Akhir - Walidaini, Birrul (IAIN Takengon, 2022)
Career planning is the process of individuals conducting an assessment of themselves and the world of work, planning steps to achieve career choices, and making rational reasoning before deciding the desired career. The purpose of this study is to find out: 1) How is the career planning of final semester students?, and 2) What are the factors that influence students in career planning?. This research was conducted using qualitative methods. The data collection techniques are observation, interviews, and literature review. Data were analyzed using data triangulation method. The informants in the research were the final semester students of the Tarbiyah faculty of IAIN Takengon totaling 15 people. The results showed that students already had career plans starting from introducing themselves and the world of work, as well as establishing communication and looking for job vacancies using internet media, finally deciding to apply for work in the desired place. Factors that influence student career planning include needs, parents and environment, interests, and skills.